Investimentos ESG: análise sobre o desempenho financeiro das empresas presentes no mercado de capitais - Figueiredo, Amanda Kethelen Lopes de (Brasil, 2024)
This article analyzes the financial performance of publicly traded organizations related to ESG criteria. Performance represents the ability of companies to generate profit with the resources available to achieve their business objectives. Furthermore, the term ESG is associated with practices focused on the environment, social responsibility and corporate governance of organizations, a topic that is increasingly present in the business world today. Therefore, the present study aimed to analyze whether companies that have ESG criteria applied in their policy present a positive financial return than those that do not. For the study, the 83 best ESG results from organizations that are listed on the Brazilian stock exchange (B3) were considered. The database considered refers to the year 2022. The relationship between the dependent variable earnings per share (LPA) and the indicators: ESG, return on assets and net margin as independent variables were evaluated. To carry out this study, the descriptive statistical method and the ordinary least squares estimation model were chosen. The statistical program determined to result in linear regression was Gretl, used in econometric research, resulting in statistical significance. The study points out that publicly traded companies that have ESG practices implemented in their business have a positive financial return. This indicates that companies that are not yet applying these criteria need to start developing and implementing this new business model to be able to attract and retain their investors.